Foundations of algorithms using C++ pseudocode - Neapolitan, Richard E.; Naimipour, Kumarss (Sudbury, Mass. : Jones and Bartlett Publishers, 1998)
Foundations of Algorithms Using C++ Pseudocode offers a well-balanced presentation on designing algorithms, complexity analysis of algorithms, & computational complexity that is accessible to mainstream computer science students who have a background in college algebra & discrete structures. To support their approach, the authors present mathematical concepts using Standard English & a simpler notation than is found in most texts. A review of essential mathematical concepts is presented in three appendices. In addition, they reinforce the explanations with numerous concrete examples to help students grasp theoretical concepts.
Rev. ed. of: Foundations of algorithms. Lexington, Mass. : D.C. Heath, c1996.
Includes bibliographical references (p. 513-515) and index.
1
Keywords: Algorithms; Constructive mathematics; Computational complexity